(untitled) (World Bulletin of Public Health, 2022)
The organs of the body connect a person with the external environment, while the internal organs themselves show the effect of the face by the fall. More than 90% of the information that enters the human body is entered by construction analyzers. Therefore, maintaining and adapting the functions of the building and the health of the building members to the society is a very important issue. In recent years, the incidence of disability due to autumn diseases has been increasing (AUTHOR).